The role of the thymus in T-cell immune reconstitution after umbilical cord blood transplantation - Politikos, Ioannis (Blood, 2014)
Umbilical cord blood (UCB) is an alternative source of hematopoietic stem cells for patients without HLA-matched adult donors. UCB contains a low number of nucleated cells and mostly naive T cells, resulting in prolonged time to engraftment and lack of transferred T-cell memory. Although the first phase of T-cell reconstitution after UCB transplantation (UCBT) depends on peripheral expansion of transferred T cells, permanent T-cell reconstitution is mediated via a central mechanism, which depends on de novo production of naive T lymphocytes by the recipient’s thymus from donor-derived lymphoid-myeloid progenitors (LMPs). Thymopoiesis can be assessed by quantification of recent thymic emigrants, T-cell receptor excision circle levels, and T-cell receptor repertoire diversity. These assays are valuable tools for monitoring posttransplantation thymic recovery, but more importantly they have shown the significant prognostic value of thymic reconstitution for clinical outcomes after UCBT, including opportunistic infections, disease relapse, and overall survival. Strategies to improve thymic entry and differentiation of LMPs and to accelerate recovery of the thymic stromal microenvironment may improve thymic lymphopoiesis. Here, we discuss the mechanisms and clinical implications of thymic recovery and new approaches to improve reconstitution of the T-cell repertoire after UCBT.